The Rate of Fulfillment of Water Fleas Intestine by Viterna Supplement With Different Water Ph, Dosage, And Enrichment Time - Sukendi Sukendi; Benny Heltonika; Ade Yulindra; Harianto Harianto (ECOTONE, 2021)
Natural food enrichment, especially water fleas, is an important effort in improving the performance of freshwater fish larvae. The enrichment process that will be carried out is influenced by several factors that need to be considered, namely the dose of vitamin supplements, pH, and time of enrichment so that the vitamins can be absorbed by the intestines and the nutritional value of water fleas increases. This study aims to examine and determine how the effect of the dose of viterna, water pH, and time of enrichment on the rate of the fulfillment of the gut of water fleas by viterna. This research was conducted from January 3 to 7, 2022 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Science, Riau University. The treatment in this study is the rate of the fulfillment of the water fleas' intestines during the water fleas natural feed enrichment technique which was carried out with three different pH test factors, different doses, and different enrichment times. The results showed that the water fleas enriched for 5 hours, at a pH of 7 and a dose of 60 ml/L of viterna showed the best filling rate of the water fleas' intestines at 100%, and the water fleas' intestines were filled with viterna compared to other treatments.